2017
DOI: 10.1016/j.amsu.2017.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Potential cost savings by minimisation of blood sample delays on care decision making in urgent care services

Abstract: BackgroundTimely availability of blood sample results for interpretation affects planning and delivery of patient care from initial assessment in Accident and Emergency (A&E) departments.Materials and methodsRates of, and reasons for, rejected blood samples submitted from all clinical areas over one month were evaluated. Haemoglobin (Hb) represented haematology and potassium (K+), biochemistry. A prospective observational study evaluated the methodology of sample collection and impact on utility.Results16,061 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
(19 reference statements)
0
6
0
Order By: Relevance
“…Nevertheless, venepuncture is an invasive technique that can cause trauma at the insertion site and can be painful for the patient, and these effects are potentiated when repeated blood samples are required (Buowari, 2013). Difficulty in finding and accessing a suitable venepuncture site can also cause a delay in treatment particularly during an emergency situation (Bodansky et al, 2017). This delay can occur despite the presence of a PIVC if the device is not permitted for use for blood samples (Ortells-Abuye et al, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Nevertheless, venepuncture is an invasive technique that can cause trauma at the insertion site and can be painful for the patient, and these effects are potentiated when repeated blood samples are required (Buowari, 2013). Difficulty in finding and accessing a suitable venepuncture site can also cause a delay in treatment particularly during an emergency situation (Bodansky et al, 2017). This delay can occur despite the presence of a PIVC if the device is not permitted for use for blood samples (Ortells-Abuye et al, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Based on US data for 2006-2008 from the national register of services within the ED (the National Hospital Ambulatory Medical Care Survey-NHAMCS), it was found that compared with interventions in the ED based on treatment, ordering any tests during the patient's stay in an ED increased its length, which was particularly noticeable when it comes to visiting patients in the ED completed discharge to home [27]. In this area, it is also worth citing an interesting analysis by Bodansky et al They showed that in as many as 40% of cases, ED doctors did not re-order tests that were initially ordered but proved impossible to be performed in the laboratory from the samples, which might suggest that routine testing is unnecessary in the first place [28]. These results confirm the validity of recommendations for prudent commissioning of laboratory tests appearing in other studies dealing with cost reduction in emergency departments.…”
Section: Discussionmentioning
confidence: 99%
“…In an emergency department study, specimen rejections have been associated with increased in-hospital stay and cost. 1 A retrospective review of incident reports in a pediatric emergency department revealed that the majority of errors occurred in the pre-analytic phase involving improper collection, labelling, or loss of specimens. 2 17.4% of patients were harmed by these errors.…”
Section: Introductionmentioning
confidence: 99%